A Wolf in Sheep's Clothing: An "Alien Leg" in Corticobasal Syndrome. (26th April 2017) - Olszewska, Diana Angelika; McCarthy, Allan; Murray, Brian; Magennis, Brian; Connolly, Sean; Lynch, Tim
Background: Alien limb phenomenon occurs in 50–60% of patients with corticobasal syndrome (CBS) and usually presents with an "alien hand" phenomenon. The "alien foot" presentation is rarer and may be misdiagnosed, as foot involvement can lead to erroneous localization of the clinical problem to the knee, hip, or back. Subsequently misdiagnoses such as myelopathy, radiculopathy, functional disorder, stiff leg syndrome, neuromyotonia, and painful leg moving toes syndrome may occur. Case report: We describe two patients with alien foot symptoms that resulted in multiple opinions from different specialists, multiple diagnostic and therapeutic procedures, and delayed diagnosis. Eventually a diagnosis of CBS was made in both. Alien foot symptoms may be more common than initially thought and can result in a delayed diagnosis of CBS. Conclusion: The inclusion of this clinical finding in recently proposed diagnostic criteria highlights the need for increased clinical awareness.